Bird communities of forests and grasslands on isolated rocky outcrops in Paraje Tres Cerros, Corrientes, Argentina - Fandiño, Blas (2017)
Isolated rocky outcrops can act as patch habitats that host great biodiversity through the diversity of microhabitats, presence of restricted taxa and the high turnover of species in the patch matrix. The isolated rocky outcrops of Paraje Tres Cerros (ARPTC), Corrientes, Argentina, are a unique landscape in the region and biologically little explored. We conducted a study to describe for the first time the bird community of the forest and grassland of the ARPTC, using 136 lists following the ten species Mackinnon method from the breeding and non-breeding seasons. We evaluated the diversity, trophic guilds and phenology of the species, and compared attributes of grassland and forest communities. The total species richness was 107, with the forest being 1.3 times more diverse than the grassland. Completeness of inventories ranged from 83-90 % in the grassland and 88 to 99 % in the forest. The habitat complementarity was 62 %, indicating the presence of several species exclusive of forest and grassland habitats. The trophic structure of communities showed a good representation of insectivorous birds in both habitats. Frugivorous birds were more frequent in the forest and granivorous birds were more frequent in the grasslands. Due to the arrival of migrant species, both habitats had significantly higher richness in the breeding season than in the non-breeding season. Our results showed similar general aspects and patterns for bird communities and with specific studies for bird communities of rocky outcrops. The present study highlights the importance of the isolated rocky outcrops of Paraje Tres Cerros for the protection of local and regional bird biodiversity and represents a benchmark for the management and the protection of these ecosystems. p>